The relationship of active teaching and learning approach with entrepreneurial intention and interest / Nik Fakrulhazri Nik Hassan, Anita Md. Shariff & Zaleha Mohamad - Nik Hassan, Nik Fakrulhazri; Md. Shariff, Anita; Mohamad, Zaleha (2010)
Entrepreneurship course at UiTM and UMT offers the students an educational experience based on active teaching and learning concept. The success of the course in improving the graduates’ intention and interest towards entrepreneurship is being studied. This research attempted to identify the contents of Entrepreneurial course that emphasize active teaching and learning approaches and their relationships towards enhancing students’ entrepreneurial intention and interest. Critical aspects of the course’s seven main contents are being tested. The course contents include business plan initial preparations, business plan developmental stage, business plan presentations, lectures and tutorial, learning materials, seminar, and examinations. Results of the test conducted with one hundred and thirty five respondents, show high validity and reliability of the questionnaire. All course contents have strong correlations with entrepreneurial intention and interest. However, Independent T-test and Oneway ANOVA indicated that the whole demographics background of respondents do not shows any significant differences with active teaching & learning, entrepreneurial interest and intention accept under institution categories and CGPA score levels with entrepreneurial interest. By the ways, respond given by respondents shown that 92 per cent supported the statement about attending entrepreneurship course will able to promoting entrepreneur profesion to them. Though, the findings could help in identifying the core element considered to have strong relationship towards developing entrepreneurial intention and interest among graduates. It is recommended that greater focus are given to these core contents particularly in fine-tuning the course syllabus and in allocating the necessary educational resources for entrepreneurial educations at higher learning institutions.